Sustainable fleet operations through integrated optimization under techno-economic shipping and environmental constraints - Nisiforou, Olympia; Alamanos, Angelos; Andres Garcia, Jorge; Papadaki, Lydia; Koundouri, Phoebe (My University, 2025)
The maritime sector faces increasing challenges as part of its ongoing transformation period towards more sustainable shipping: There is a shift in fuel preferences, with a gradual phasing out of high-polluting options in favor of cleaner, more sustainable alternatives, amidst increasingly stringent environmental policies pushing for greenhouse gases (GHG) emissions reduction, on top of the already complex technoeconomic considerations for optimal shipping operations. These multifaceted challenges call for sophisticated, holistic solutions that can address economic, environmental, and operational aspects simultaneously. In response, the Global Climate Hub (GCH – an initiative under the UN Sustainable Development Solutions Network) develops integrated models to assess such problems and provide sustainable pathways. Here, we present such a model, the MaritimeGCH, a free, open-source, simple and comprehensive tool to address such challenges of maritime fleet management. MaritimeGCH integrates different techno-economic, environmental, operational factors and recent European environmental policies into a single, comprehensive model, which is at the same time simple and transferable to various scales. The optimization logic is first described for maritime problems; next the detailed mathematical description of MaritimeGCH model is presented; and finally, its potential for policyrelevant scenario analysis is outlined with specific examples. The model is publicly available to encourage similar applications and improvements.
Keywords: MaritimeGCH; Global Climate Hub; Fleet Optimization; Shipping; Sustainable maritime operations; Environmental regulations; Techno-economic analysis